Finite Element Studies of Ambuklao and Caliraya Dams - Borja, Ronaldo I. (Philippine Engineering Journal; Vol 7 No 1 (1986), 2021)
In the last two decades the finite element method has experienced tremendous growth in both theoretical developments and applications. This paper explores the usefulness of this numerical method in the area of geotechnical engineering, incorporating into the implementation complex factors that cannot readily be handled by closed-form procedures such as dynamic behavior, material non homogeneities, plasticity, and creep. Subjects of the studies were two hydroelectric power-generating dams in the Philippines, namely, Ambuklao and Caliraya. Eigenvalue studies were performed of Ambuklao Dam to investigate its dynamic response to the ground shaking induced by the earthquake of April, 1985. A creep analysis of Caliraya Dam was also carried out using the conventional incremental plasticity theory and a recently developed constitutive model to predict the dam’s time-dependent deformation behavior in the next 40 years.